JC polyomavirus nephropathy, a rare cause of transplant dysfunction: Case report and review of literature. Issue 2 (22nd February 2017) - Yang, Doyle; Keys, Brandon; J. Conti, David; Foulke, Llewellyn; Stellrecht, Kathleen; Cook, Linda; Lopez‐Soler, Reynold I.
Abstract: JC polyomavirus‐associated nephropathy (JC‐PVAN) is a rare but challenging cause of renal dysfunction. We report JC‐PVAN in a renal allograft recipient and highlight the obstacles in definitive diagnosis of this disease entity. A deceased‐donor renal transplant recipient was diagnosed with JC polyomavirus nephritis 4 years after transplantation. Immunosuppressive agents were subsequently reduced, resulting in an initial stabilization of renal function. We present this interesting case and discuss the challenges with diagnosing and treating this rare entity.